Analisis Peranan Jati Diri Koperasi Sebagai Wujud Pengimplementasian Good Corporate Governance (GCG) Koperasi di Indonesia - Kgs. M. Nurkholis; Vhika Meiriasari; R.M. Rum Hendarmin (Universitas Indo Global Mandiri, 2023)
The long history of cooperatives that existed in the pre-independence era required cooperatives to always make formulas in the form of standard rules that were systematically compiled by the government and other authorities so that cooperatives could continue to play a role in building the nation's economy which has been reflected in the identity of cooperatives. Cooperative identity is reflected in three approaches, namely the essentialist approach, the institutional approach and the nominalist approach. The identity of a cooperative is actually a complex conceptual arrangement so that if the identity of a cooperative is properly implemented, a true cooperative will run according to its main corridor, namely the welfare of its members and society. Governance systems or devices known as Good Corporate Governance according to The Organization Cooperation and Development (OCD) consist of principles and characteristics that can be used as a whole (universal) consisting of culture, environmental differences and systems of laws and regulations and values -values that exist and apply in a country. Based on several studies, the researchers concluded that this crisis occurred due to a failure in implementing good corporate governance. However, there is one solution in alleviating the economic crisis, in which there is a role for the people to help each other and work together in creating a sovereign economy. which complement each other. This cannot be separated because the identity of cooperatives has become a characteristic of cooperatives from the times when ideas about cooperatives have developed and spread throughout the world. Keywords: Identity, Cooperative, Good Corporate Governance